Dinamika Partai Nahdlatul Ulama dalam Konstelasi Politik di Kabupaten Cirebon Tahun 1952-1955 - Ahmad Faiz Rofi'i (UIN Sunan Gunung Djati Bandung, 2023)
Nahdlatul Ulama is an Islamic organization founded by traditional ulama in Surabaya in 1926. During its development, NU had implemented organizational development by establishing NU branches throughout Indonesia, one of which was Cirebon succeeding in holding the 6th Congress in 1931. NU's existence in Cirebon livened up the organization exchange in this area because in the previous years religious organizations such as SI and PUI had existed. At its inception, NU only focused on religion and education, but in its development, NU has participated in national political movements. The aim of this research is to describe the history and development of the NU branch of the Cirebon Regency. Methods conducted in this research are historical methods, namely heuristics, criticism, interpretation and historiography. The results of this study reveal that a number of important facts that the presence of the local kiai determines the extent to which NU can develop and even become the main actor in NU's victory in the 1955 elections in Cirebon Regency as the winning party and the only branch in West Java that won the most votes. Kata Kunci: Cirebon, Nahdlatul Ulama, Islamic party